Technological opportunities for procedural justice in welfare administration: A review of available apps. (November 2020) - Cook, Kay; Given, Lisa; Keam, Georgia; Young, Lisa
Welfare agencies are increasingly turning to technology to facilitate information-sharing and communication with users. However, while the administrative, governmental and material effects of technological advances have been examined, research has yet to explore how welfare users could make use of technology for their benefit. In this article, we examine the extent to which available technologies allow Australian separated mothers to assemble and provide data to government agencies in order to pursue procedural, and therefore substantive, justice in child support and welfare contexts. We find that no currently available apps provide separated mothers with technological affordances suited to this purpose. As a result, we find that existing child support and welfare data practices reinforce the social hierarchies that exist post-separation, whereby low-income single mothers are financially and socially disadvantaged, while welfare administrators and non-compliant ex-partners accrue savings and discretionary benefits as a result of existing bureaucratic data gaps and omissions.